Nandrolone decanoate causes uterine injury by changing hormone levels and sex steroid receptors in a dose- and time-dependent manner - Simão, Vinícius Augusto [UNESP]; Lupi Júnior, Luiz Antonio [UNESP]; Adan Araujo Leite, Gabriel; Cherici Camargo, Isabel Cristina [UNESP]; de Almeida Chuffa, Luiz Gustavo [UNESP] (Elsevier, 2021)
Different doses of nandrolone decanoate (ND) were used to investigate the expression of uterine sex steroid receptors (AR, ER-α, and ER-β) and the levels of serum sex hormones after treatment and recovery periods in adult rats. ND doses of 1.87, 3.75, 7.5, or 15 mg/kg b.w. or mineral oil (control group) were injected subcutaneously for 15 days, and the experimental groups were divided into three periods of evaluation: (a) ND treatment for 15 days, (b) ND treatment followed by 30-day-recovery and (c) ND treatment followed by 60-day-recovery. Estrous cycle was monitored daily. At the end of each experimental period, rats were euthanized for the collection of serum samples and uterine tissues. All animals showed persistent diestrus and only the highest ND dose was capable of inducing persistent diestrus until 60-day-recovery. Immunoexpression of uterine sex steroid receptors varied in a time-dependent manner. While AR expression was increase after treatment period, ER-α and ER-β expressions decreased after 60- and 30-day-recovery, respectively. ND also increased the serum levels of testosterone, 17β-estradiol, and dihydrotestosterone, especially at the highest doses of 7.5 and 15 mg ND/kg until 30 days of recovery. The levels of progesterone were significantly reduced in all ND-treated animals. No significant difference was observed in the levels of follicle-stimulating hormone, whereas the levels of luteinizing hormone varied according to specific dose and period. We conclude that uterine sex steroid receptors and sex hormones are affected by ND administration and these alterations can be only restored following lower doses and long recovery periods.
Keywords: Anabolic-androgenic steroid; Nandrolone decanoate; Rats; Recovery period; Uterus